2012
DOI: 10.1007/s11042-012-1098-9
|View full text |Cite
|
Sign up to set email alerts
|

Open annotations on multimedia Web resources

Abstract: Many Web portals allow users to associate additional information with existing multimedia resources such as images, audio, and video. However, these portals are usually closed systems and user-generated annotations are almost always kept locked up and remain inaccessible to the Web of Data. We believe that an important step to take is the integration of multimedia annotations and the Linked Data principles. We present the current state of the Open Annotation Model, explain our design rationale, and describe ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The goal of this model was to connect the original resource to the archived version of that resource to cater for the fact that a resource could change over time [53,93].…”
Section: Mementomentioning
confidence: 99%
“…The goal of this model was to connect the original resource to the archived version of that resource to cater for the fact that a resource could change over time [53,93].…”
Section: Mementomentioning
confidence: 99%
“…The result indicated that 35-90% of publicly accessible URIs have at least one archived copy, although they did not consider annotations in their work, the result might estimate the number of orphaned annotations by factors like how frequently web pages are archived and the archiving process coverage. In other work [17,11] researchers built annotation systems that can deliver a better user experience for specialized users and scholars. The interfaces allow users to annotate multimedia web resources as well as medieval manuscripts in a collaborative way.…”
Section: Related Workmentioning
confidence: 99%
“…Learner Group 1 is asked to annotate the BPM life cycle that can be found in "Modeling foundations" with examples according to their own experiences and background (cf. [47]). These annotations together with the other resources are passed on to Learner Group 2 to accomplish a practical BPM modeling task, namely Process Analysis for a service industry.…”
Section: Stakeholder-centered Ontologies For Educational Designsmentioning
confidence: 99%